2015
DOI: 10.14257/ijhit.2015.8.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Game Adoption in China: the Role of TAM and Perceived Entertainment, Cost, Similarity and Brand Trust

Abstract: The mobile game is experiencing a rapid development and one of the favorite mobile applications. This article focuses on Chinese mobile game market and conducts an empirical research on the factors of the user adoption of mobile game. The research results show that perceived usefulness, perceived entertainment, economic cost and subject norm significantly affect the attitude of use, which results in behavior intention to adopt the mobile game, while the perceived ease of use, similarity and brand trust, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
3
10
0
1
Order By: Relevance
“…Here, an explanation of the lack of effect may be based on the simplicity of the tool and loss of usefulness of these apps when the replacement exists, such as an online version or by Web. These results are also consistent with Jiang, Peng, and Liu (2015); the authors identify usefulness of mobile games as a construct that contribute to improve the life of a person via other aspects as enjoyment or entertainment, which would justify the positive relationship on attitude toward the system.…”
Section: Final Discussion Limitations and Future Researchsupporting
confidence: 87%
“…Here, an explanation of the lack of effect may be based on the simplicity of the tool and loss of usefulness of these apps when the replacement exists, such as an online version or by Web. These results are also consistent with Jiang, Peng, and Liu (2015); the authors identify usefulness of mobile games as a construct that contribute to improve the life of a person via other aspects as enjoyment or entertainment, which would justify the positive relationship on attitude toward the system.…”
Section: Final Discussion Limitations and Future Researchsupporting
confidence: 87%
“…Moreover, various researchers also identified the importance of informativeness and positive relationship among informativeness, attitude and behavioral intention (Haq, 2009) and it is measured as a vital construct for having a significant effect on attitude of individuals (Gvili & Levy, 2016). Antecedents of positive user behavior were examined and the results exposed that informativeness is a key driver of favorable behavioral response and intention to involve in satisfactory user reactions which is positively related with intention to purchase (Jiang, Peng, & Liu, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Muñoz et al (2017) found several variables, such as perceived usefulness towards intention to use, are weak. Another study that uses TAM from the mobile games' perspective found that all variables are significantly influencing behavioural intention to adopt the mobile game (Jiang, Peng & Liu, 2015;Murphy et al, 2016). These show that TAM is used continuously by researchers to explain which factor influences user acceptance or rejection of mobile application regardless of the field of study.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 97%